Career guidance in Denmark : Social control in a velvet glove - Plant, Peter; Thomsen, Rie (2011)
La Orientación Vocacional en Dinamarca está bien organizada y es altamente profesional. Esto refleja una política orientadora centrada en el papel que la orientación juega como instrumento en el ejercicio de un leve control social. Con este telón de fondo, el dilema de la Orientación en Dinamarca reside en el delicado equilibrio existente entre la orientación considerada como una herramienta para el desarrollo personal, y como un instrumento de control social.
Career guidance in Denmark is well organised, highly structured, and professionalised. This mirrors the strong policy focus on the role of guidance as a soft societal steering instrument. With this backdrop, the dilemma in Danish guidance is the delicate balance between guidance as an instrument for personal development, and guidance as social control.
Keywords: Orientación; Políticas orientadoras; Control social